KOMPETENSI PENGEMBANGAN KEPRIBADIAN DAN KEPROFESIONALAN PADA GURU PENDIDIKANJASMANI (KOMPETENSI PENTING YANG MASIH TERABAIKAN) - Margono, - (Jurnal Pendidikan Jasmani Indonesia, 2006)
Abstract. PJKR 2002 curriculum was made with goals to prepare teachers with capability ofacademic and professional in physical education that can integrate teaching education,education science, physical science, learning science, and have personality andprofessional skill to bring education and teaching process. Ditjen Dikti has four competencecomponents as the requirement for physical education teacher: (1) Mastering subject matter,(2) Understanding of the students, (3) Mastering good educational learning process, and(4) Development of personality and professionalism. Competence aspects of no.1,2 and 3has been well accommodate in 2002 curriculum. However, the competence aspects no.4which is development of personality and professionalism has not been accommodate (in away that it is taught in related subject matter to accomplish it). However, this aspects needspecial attention due to 10 competence of its breakdown is an important base to contributeto personal development. Several activities can be done are: optimizing certain subjectmatter teaching process, to integrate the competence achievement to certain subject matter,intensive partnership with lecturer from outside POR major, have conditions of certainphysical condition, etc. There are many homework to do but there are a priority to beestablish.Keyword: teacher, physical education, competence, professional.